The influence of high-k passivation layer on breakdown voltage of Schottky AlGaN/GaN HEMTs. Issue 12 (December 2015) - Jebalin, Binola K.; Shobha Rekh, A.; Prajoon, P.; Kumar, N.Mohan; Nirmal, D.
Abstract: In this work, analysis and optimization of different high-k material in the passivation layer is carried out to improve the breakdown voltage in a Schottky based AlGaN/GaN High Electron Mobility Transistor (HEMT). The enhancement in Off-state breakdown voltage is observed for different high-k dielectric in the passivation layer. The device with L gd of 1.5 µm and with high-k passivation layer provides a higher Off-state breakdown voltage. A maximum of 380 V is obtained as the Off-state breakdown for high-k ( HfO2 ) passivation layer and the obtained result is validated using experimental data. The improved drain current and transconductance for the device obtained is 0.51 A/mm and 143 mS/mm respectively. These results show that the Schottky Source Drain contact (SSD) high-k passivated AlGaN/GaN device is suitable for high power application.